2011
DOI: 10.3109/09638288.2011.591890
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative rehabilitation approaches in those over 75 years with respiratory dysfunction from chronic obstructive pulmonary disease undergoing abdominal tumor surgery

Abstract: Comprehensive perioperative rehabilitation appears to be effective in high-risk patients with severe COPD who need surgery for abdominal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…However, we emphasize that we found that respiratory complications were more common among non-survivors overall and therefore agree with others that predicting postoperative pulmonary complications can facilitate the selection of those patients that could benefit from specific evaluation and preparation for surgery [26] as well as increased vigilance on the ward [12]. Preoperative physical therapy has been found useful in preventing respiratory complications [27]. …”
Section: Discussionsupporting
confidence: 88%
“…However, we emphasize that we found that respiratory complications were more common among non-survivors overall and therefore agree with others that predicting postoperative pulmonary complications can facilitate the selection of those patients that could benefit from specific evaluation and preparation for surgery [26] as well as increased vigilance on the ward [12]. Preoperative physical therapy has been found useful in preventing respiratory complications [27]. …”
Section: Discussionsupporting
confidence: 88%
“…These programs have been used mainly before orthopedic surgery with improvement of health outcomes (18). In oncologic patients, prehabilitation has been used as a useful tool to improve patient's evolution, but mainly before surgical intervention (19), and its positive effects on the quality of life (QoL) as well as general outcomes have been also described in elderly cancer survivors (20). Reports on the bene ts of prehabilitation in non-surgical cancer patients are scarce.…”
Section: Discussionmentioning
confidence: 99%